Design and Synthesis of Selurampanel, a Novel Orally Active and Competitive AMPA Receptor Antagonist. (15th November 2016) - Orain, David; Tasdelen, Engin; Haessig, Samuel; Koller, Manuel; Picard, Anne; Dubois, Celine; Lingenhoehl, Kurt; Desrayaud, Sandrine; Floersheim, Phillip; Carcache, David; Urwyler, Stephan; Kallen, Joerg; et al.
Abstract: A series of potent quinazolinedione sulfonamide antagonists of the α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole‐propionic acid (AMPA) receptor were designed and synthesized. The structure–activity relationships (SAR) and in vivo activity of the series were investigated. In particular, compound1 S (selurampanel; N ‐[7‐isopropyl‐6‐(2‐methylpyrazol‐3‐yl)‐2, 4‐dioxo‐1 H ‐quinazolin‐3‐yl]methanesulfonamide) has shown excellent oral potency against maximal electroshock seizure (MES)‐induced generalized tonic–clonic seizures in rodents as well as significant activity in patients suffering from various forms of epilepsy. The X‐ray crystal structure of selurampanel bound to the AMPA receptor hGluA was also obtained. Abstract : Strong anticonvulsant : We report the design and synthesis of the AMPA receptor antagonist selurampanel. The X‐ray crystal structure of selurampanel bound to the AMPA receptor hGluA, which is also described, highlights the interactions of the compound with hGluA. This compound has shown excellent oral potency against MES‐induced generalized tonic–clonic seizures in rodents as well as significant activity in patients suffering from various forms of epilepsy.